A Philosophical Analysis of Islamic Education: Nature, Objectives, and Principles from the Qur’an and Sunnah Perspective - Alfian; Dwi Meli Noviani (Penerbit Hellow Pustaka, 2026)
This study aims to philosophically analyze the nature, objectives, and principles of Islamic education from the perspective of the Qur’an and Sunnah. The research employs a qualitative approach using a library research method by examining various relevant primary and secondary sources. The findings reveal that Islamic education is a holistic process oriented toward developing human innate potential (fitrah) in a balanced manner, encompassing spiritual, intellectual, and moral dimensions. The primary goal of Islamic education is to form insan kamil (the perfect human), characterized by the integration of faith, knowledge, and action, as well as the ability to fulfill the roles of servant of God and vicegerent on earth. The principles of Islamic education are grounded in the Qur’an and Sunnah and are implemented through an integrated approach that includes cognitive, affective, and psychomotor domains. Furthermore, Islamic education is required to adapt to contemporary developments without losing its fundamental values. Therefore, Islamic education functions not only as a means of knowledge transfer but also as a value system that shapes the character and morality of learners comprehensively.